The popularization of orodispersible tablets in the pharmaceutical market - Ludmila Alvim PINHO; Ana Claudia TEMER; Caroline RIBEIRO; Livia Lira SÁ-BARRETO; Marcilio Sergio Soares CUNHA-FILHO (Federal Council of Pharmacy, 2018)
Orodispersible tablets are getting popular due to its easy administration which leads to a higher therapeutic adherence. This study aimed to evaluate the state of the art of these drug products based on the scientific literature. Also, orodispersible tablets available in the US, Europe and Brazil markets based on information extracted from the health agencies were analyzed. Those tablets are designed to be placed on the tongue and instantly disintegrated by the fast capitation of the saliva without the additional intake of water. The orodispersible technology enables oral administration of tablets to patients with dysphagia, especially children, and elderlies. Moreover, orodispersible make possible rapid drug intervention and mouth absorption. The drug is partially absorbed in the oral cavity, pharynx, and esophagus without first pass effect, increasing drug bioavailability and reaching faster therapeutic effect. This is a low-cost technology that fits in a conventional solid production area and adds value to the product without requiring high investment. A market analysis showed there is a predominance of antihistamine drugs or medicines for mental disorders using orodispersible matrices. However, the orodispersible technology shows great versatility and potential application to other pharmacological groups. It is expected that in coming years a massive commercial insertion of this tablet technology occurs. In this scenery, it is indispensable that health professionals are prepared with updated technical information for the use of this therapeutic resource safely and efficiently.